The Process and Impact of Entrepreneurial Learning in the Home Industry Community in Increasing Family Economic Income - Khamidah, Anisa; Yusuf, Amin; Shofwan, Imam; Sabah, Mustafa Ismail Khudair (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
Home industries face complex challenges, especially in terms of poverty and social inequality. This research aims to describe the learning process and its impact on family economic welfare through a study of three enterprises that are members of a community, namely Zasna Souvenir, Nadira Souvenir and Hana Bag. This study employed a descriptive qualitative approach, utilizing in-depth interviews, observations, and documentation techniques to collect data. A total of six respondents, consisting of three home industry managers and three employees or community members, were selected to gain diverse perspectives. The collected data were analyzed using the interactive data analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing to ensure the credibility and depth of the research findings. The results show that the learning process in home industry includes the stage of promoting familiarity, the stage of identifying learning needs, the stage of formulating learning objectives, the stage of preparing learning programs, the stage of implementing learning programs, the stage of evaluating learning programs. The impact of this learning process not only fulfills basic needs, but also supports education, health, home improvement and social activities. The research findings show that the souvenir bag home industry community is an innovative solution to increase family economic income while fostering an experiential learning environment.  This learning model enables community members to acquire practical skills, foster creativity and increase productivity, ultimately increasing their family's economic income. In addition, this research contributes to identifying an effective experiential learning model in small community-based enterprises, which can be adapted by other enterprises to sustainably improve the local economy. As this model has not been widely tested in the context of cottage industries in Indonesia, it is imperative to explore its applicability and analyze its potential impact on the economic growth of local communities. The insights provided by this research offer a valuable contribution to the development of sustainable learning practices that support community-based entrepreneurship and strengthen the economic independence of small enterprises, especially within the framework of home industries in Indonesia.